2015
DOI: 10.1128/jvi.03275-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Type I Interferon Signaling in Human Metapneumovirus Pathogenesis and Control of Viral Replication

Abstract: Type I IFN signaling, which is initiated through activation of the alpha interferon receptor (IFNAR), regulates the expression of proteins that are crucial contributors to immune responses. Paramyxoviruses, including human metapneumovirus (HMPV), have evolved mechanisms to inhibit IFNAR signaling, but the specific contribution of IFNAR signaling to the control of HMPV replication, pathogenesis, and adaptive immunity is unknown. We used IFNAR-deficient (IFNAR ؊/؊ ) mice to assess the effect of IFNAR signaling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 83 publications
(95 reference statements)
2
47
0
Order By: Relevance
“…151 In fact, hMPV infected-IFNAR¡/¡ mice had a higher peak of early viral replication, less airway dysfunction and lung inflammation, but cleared the virus with the same kinetics as observed in WT mice. 151 Likewise, CD8 C T cells from IFNRA¡/¡ mice expressed similar levels of PD-L1 when compare with CD8 C T cells from WT mice. However, these cells showed an upregulation of the inhibitory receptor TIM-3, thus impairing the CD8 C T cell function.…”
Section: Cd8mentioning
confidence: 91%
See 1 more Smart Citation
“…151 In fact, hMPV infected-IFNAR¡/¡ mice had a higher peak of early viral replication, less airway dysfunction and lung inflammation, but cleared the virus with the same kinetics as observed in WT mice. 151 Likewise, CD8 C T cells from IFNRA¡/¡ mice expressed similar levels of PD-L1 when compare with CD8 C T cells from WT mice. However, these cells showed an upregulation of the inhibitory receptor TIM-3, thus impairing the CD8 C T cell function.…”
Section: Cd8mentioning
confidence: 91%
“…However, these cells showed an upregulation of the inhibitory receptor TIM-3, thus impairing the CD8 C T cell function. 151 Additionally, CD8 C T cells can be impaired by hMPV in a PD-1 dependent manner, similar to hRSV, as lung CD8 C T cells are impaired in HLA B7.2 transgenic (B7tg) mice and had upregulated PD-1. 152 Conversely, blocking of PD-1 by administration of monoclonal specific antibodies in B7tg mice prevented the CD8 C T cells impairment.…”
Section: Cd8mentioning
confidence: 99%
“…WT mice treated with IFNAR-blocking antibody or mice genetically deficient in IFNAR are currently popular animal models for investigating the immune response and pathogenesis of ZIKV infection (5, 6), although two papers reported recently that CD8 ϩ T cells could be activated by ZIKV infection in B6 WT mice (8,9). Numerous studies have demonstrated that type I interferon (IFN) deficiency impaired the CD8 ϩ T cell response during virus infection through many cellular and molecule mechanisms, such as by impairing the priming effect of dendritic cells and upregulating the expression of the inhibitory molecules PD-1 and Tim3 of CD8 ϩ T cells during virus infection (10,12,13). In addition, because of the deficiency of innate immune components, the IFNAR knockout (KO) mouse model could exclude a comprehensive study of the immune response (14,15) and did not reflect the natural immune response after infection.…”
Section: Resultsmentioning
confidence: 99%
“…IFNAR-2c has an important role in ligand binding and signal transduction process, while IFNAR-2a and 2b are competitive inhibitors that prevent IFNα binding into IFNAR-2c. 3,4 hIFNα2 is produced by leukocytes and consists of 16 types. hIFNα2a, as one of hIFNα2 member, is widely known to have a very broad biological activity as antiviral, antiproliferative, and immunomodulative therapeutic.…”
Section: Introductionmentioning
confidence: 99%